A comparison of three dimensional change in maxillary complete dentures between conventional heat polymerizing and microwave polymerizing techniques - Shinsuke Sadamori; Toshiya Ishii; Taizo Hamada; Arifzan Razak (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
The purpose of this study was to measure and compare two different polymerizing processes, heat polymerizing (HP) and microwave polymerizing (MP), on the three dimensional changes in the fitting surface and artificial teeth of maxillary complete dentures. A threedimensional coordinate measurement system was used to record distortion of the specimens. The distortion of the fitting surface was measured from the reference plane on the fitting side from which a coordinate system was set, and the movement of the artificial teeth and the distortion of the polished surface was measured from the reference plane of the artificial tooth side, from which a coordinate system was set. It was clearly showed that various distortions of denture specimens after polymerization process can be measured with this three-coordinate measuring machine. The study showed that the overall distortion of the fitting surface in HP specimens was shown to be larger than in MP ones.